Completeness and timeliness of tuberculosis notification in Taiwan - Lo Hsiu-Yun; Yang Shiang-Lin; Chou Pesus; Chuang Jen-Hsiang; Chiang Chen-Yuan (BMC, 2011)
Abstract Tuberculosis (TB) is a notifiable disease by the Communicable Disease Control Law in Taiwan. Several measures have been undertaken to improve reporting of TB but the completeness and timeliness of TB notification in Taiwan has not yet been systemically evaluated. Methods To assess completeness and timeliness of TB notification, potential TB cases diagnosed by health care facilities in the year 2005-2007 were identified using the reimbursement database of national health insurance (NHI), which has 99% population coverage in Taiwan. Potential TB patients required notification were defined as those who have TB-related ICD-9 codes (010-018) in the NHI reimbursement database in 2005-2007, who were not diagnosed with TB in previous year, and who have been prescribed with 2 or more types of anti-TB drugs. Each potential TB case was matched to the national TB registry maintained at Taiwan Centers for Disease Control (CDC) by using national identity number or, if non-citizen, passport number to determine whether the patients had been notified to local public health authorities and Taiwan CDC. The difference in the number of days between date of anti-tuberculosis treatment and date of notification was calculated to determine the timeliness of TB reporting. Results Of the 57,405 TB patients who were prescribed with 2 or more anti-tuberculosis drugs, 55,291 (96.3%) were notified to National TB Registry and 2,114 (3.7%) were not. Of the 55,291 notified cases, 45,250 (81.8%) were notified within 7 days of anti-tuberculosis treatment (timely reporting) and 10,041(18.2%) after 7 days (delayed reporting). Factors significantly associated with failure of notification are younger age, previously notified cases, foreigner, those who visited clinics and those who visited health care facilities only once or twice in 6 months. Conclusion A small proportion of TB cases were not notified and a substantial proportion of notified TB cases had delayed reporting, findings with implication for strengthening surveillance of tuberculosis in Taiwan. Countries where the completeness and timeliness of TB notification has not yet been evaluated should take similar action to strengthen surveillance of TB.